The Role of Pancreatic Alpha Cells and Endothelial Cells in the Reduction of Oxidative Stress in Pseudoislets - Wieland, Fredrik C.; Sthijns, Mireille M.J.P.E.; Geuens, Thomas; van Blitterswijk, Clemens A.; LaPointe, Vanessa L.S. (Frontiers in Bioengineering and Biotechnology, 2021)
Pancreatic beta cells have inadequate levels of antioxidant enzymes, and the damage induced by oxidative stress poses a challenge for their use in a therapy for patients with type 1 diabetes. It is known that the interaction of the pancreatic endocrine cells with support cells can improve their survival, making these important interactions to study. but have shown less vulnerability to oxidative stress when they are cocultured with other support cells such as alpha or endothelial cells. Here we investigated alpha (alpha TC-1), beta (INS1E) and endothelial (HUVEC) cells assembled into aggregates known as pseudoislets as a model of the pancreatic islets of Langerhans. We hypothesized that the coculture of alpha, beta and endothelial cells would be protective against oxidative stress. First, we showed that adding endothelial cells decreased the percentage of oxidative stress–positive cells. We then asked if the number of endothelial cells or the size (number of cells) of the pseudoislet could increase the protection against oxidative stress. However, no additional benefit was observed by those changes. On the other hand, we identified a potential supportive effect of the alpha cells in reducing oxidative stress in beta and endothelial cells. We were able to link this to the incretin glucagon-like peptide-1 (GLP-1) by showing that the absence of alpha cells in the pseudoislet caused increased oxidative stress, but the addition of GLP-1 could restore this. Together, these results provide important insights into the roles of alpha and endothelial cells in protecting against oxidative stress.